2018
DOI: 10.1103/physrevlett.120.208005
|View full text |Cite
|
Sign up to set email alerts
|

Strand Plasticity Governs Fatigue in Colloidal Gels

Abstract: The repeated loading of a solid leads to microstructural damage that ultimately results in catastrophic material failure. While posing a major threat to the stability of virtually all materials, the microscopic origins of fatigue, especially for soft solids, remain elusive. Here we explore fatigue in colloidal gels as prototypical inhomogeneous soft solids by combining experiments and computer simulations. Our results reveal how mechanical loading leads to irreversible strand stretching, which builds slack int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 30 publications
8
24
0
Order By: Relevance
“…Moreover, the observation that the fingering characteristics are set solely by the properties of the fully fluidized state of the sample might shed light on discrepancies pointed out in [32], where the finger width observed in hair gel solutions is independent of their yield stress. More generally, the local fluidization scenario described here is in line with recent rheological work on stress-induced failure in gels [56], suggesting that our critical energy criterion could be relevant for predicting the outcome of delayed failure in colloidal gels [57,58]. However, our results strongly contrast with experiments on jammed assemblies of soft particles such as dense microgels for which the wavelength of the pattern is set by the yield stress of the material [29].…”
supporting
confidence: 87%
“…Moreover, the observation that the fingering characteristics are set solely by the properties of the fully fluidized state of the sample might shed light on discrepancies pointed out in [32], where the finger width observed in hair gel solutions is independent of their yield stress. More generally, the local fluidization scenario described here is in line with recent rheological work on stress-induced failure in gels [56], suggesting that our critical energy criterion could be relevant for predicting the outcome of delayed failure in colloidal gels [57,58]. However, our results strongly contrast with experiments on jammed assemblies of soft particles such as dense microgels for which the wavelength of the pattern is set by the yield stress of the material [29].…”
supporting
confidence: 87%
“…The observed divergence of fluctuations then translates into a maximum entropic contribution to the stress, which could manifest in the rheology of these larger networks. Our results open up unique avenues for self-assembled colloidal structures with advanced nonlinear mechanics of relevance for the understanding of the rheology of gels [9], the mechanics of living tissues [16] and of designer colloidal architectures [17]. For the optical tweezers, laser light of 1064nm was used at a power of 20±5mW.…”
mentioning
confidence: 99%
“…We have shown that colloidal gels undergo syneresis when eliminating adhesive boundary conditions and forming gels in situ. Interestingly, we observe that the magnitude of syneresis, ∆V /V 0 , is highly dependent on the surface mobility and local deformability of the particle composing the gel; these two properties are nearly universally overlooked in colloidal materials, yet, they likely play key roles in rheologic responses, especially during mechanical breakdown [32]. While syneresis is more readily seen in 'soft' particle gels, especially foods, we have shown that it is still not negligible in gels composed of solid particles, but often not observed experimentally due to adhesive container walls.…”
Section: K0kmentioning
confidence: 90%